Galiza Seen by Archer Milton Huntington: A Note-Book in Northern Spain (1898) - López, Teresa (Madrygal. Revista de Estudios Gallegos, 2020)
In 1898, Archer Milton Huntington, future founder of the Hispanic Society of America, published A Note-Book in Northern Spain, a travel book whose initial chapters are dedicated to Galicia, especially to Coruña and Santiago de Compostela. The aim of this article is to analyze the image of Galicia captured in the volume, within the framework of the representation of Spain built by the Anglo-Saxon gaze, particularly the North American one, reflected in travel literature, in the incipient Hispanic academic production and in the Spanish Craze, that spans the arts in the United States at the turn of the century, coinciding with a time of political conflict between the two states. We will show how A Note-Book in Northern Spain combines the direct impressions of the traveler about Galicia with the information obtained from book sources, very uniquely from Galicia (1888) by Manuel Murguía, a reference work of Galician regionalism, and of Recuerdos de un viaje a Santiago de Galicia (1880) by Fidel Fita and Aureliano Guerra, of the Jacobean studies.The analysis will take into account additional information on Huntington's trips to Spain and Galicia, collected in his diaries.
Keywords: Archer Milton Huntington; Travel Literature; Anglo-Saxon Travellers; Galician Identity